2010
DOI: 10.1186/1471-230x-10-96
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan present in brown algae induces apoptosis of human colon cancer cells

Abstract: BackgroundFucoidan is a sulfated polysaccharide found in brown algae; it has been shown to exhibit a number of biological effects, including anti-tumor effects. In this study, we evaluated the effects of fucoidan on apoptosis in HT-29 and HCT116 human colon cancer cells.MethodsHT-29 and HCT116 cells were cultured with various concentrations of fucoidan (0 - 20 μg/mL). Apoptosis was assayed via Hoechst staining and Annexin V staining followed by flow cytometric analysis. Western blot analyses and JC-1 staining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
187
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(204 citation statements)
references
References 41 publications
7
187
1
6
Order By: Relevance
“…A number of genes that are associated with apoptotic cell death were tested in order to clarify the mechanism by which fucoidan treatment induces apoptosis in MDA-MB-231 cells. According to some previously conducted studies, caspases act as key players of fucoidan-induced apoptosis [20][21][22][23][24][25][26][27] . These findings have guided the researcher to propose a model in which fucoidan promotes apoptosis in MDA-MB-231 cells through increasing caspases activity.…”
Section: Discussionmentioning
confidence: 99%
“…A number of genes that are associated with apoptotic cell death were tested in order to clarify the mechanism by which fucoidan treatment induces apoptosis in MDA-MB-231 cells. According to some previously conducted studies, caspases act as key players of fucoidan-induced apoptosis [20][21][22][23][24][25][26][27] . These findings have guided the researcher to propose a model in which fucoidan promotes apoptosis in MDA-MB-231 cells through increasing caspases activity.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study described that caspases are classified based on either initiator or effector caspases in apoptosis (Kim et al 2010). Initiator caspases, caspase-8 and -9, are phosphorylated by a variety apoptotic signals (Kim et al 2010). Activated or cleaved caspase-3 is an essential effector for induction of apoptosis (Xue et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Bax gene product dimerizes with Bcl-2 and controls cell death by activating caspase-3 (Seol et al 2001). The previous study described that caspases are classified based on either initiator or effector caspases in apoptosis (Kim et al 2010). Initiator caspases, caspase-8 and -9, are phosphorylated by a variety apoptotic signals (Kim et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular mass of fucoidan is heterogenic (10 -1000 kDa) and difficult for making measurement standards in studying of its biological activity. The molecular mechanism of fucoidan's anti-tumor [2], LDL cholesterol lowering [3], blood anti-coagulating [4], anti-oxidant and anti-inflammatory [5], anti-viral [6] and contraceptive [7] activities have not yet been revealed in detail. It has been reported that fucoidan is absorbed in an undigested form and displays thereafter all beneficial activities.…”
Section: Introductionmentioning
confidence: 99%